The influence of tree species and edge effects on pheromone trap catches of oak processionary moth Thaumetopoea processionea (L.) in the U.K. (20th July 2018) - Williams, David T.; Jonusas, Gillian
Abstract: Many factors influence the efficiency of insect pheromone trapping systems. In particular, captures of male oak processionary moth (OPM) Thaumetopoea processionea in pheromone traps can be highly variable, hence, two trials were conducted to determine whether the tree species in which traps are positioned or edge effects are influential factors in OPM pheromone trapping. In a 'host plant trial', pheromone traps that were positioned in the canopy of pedunculate oak ( Quercus robur ) trees captured significantly more male OPM than traps positioned in any of the other six tree species (including other species of oak) used in the trial over two successive years. In an 'edge effects trial', pheromone traps positioned on the edges of oak woodland blocks captured more moths than traps positioned within the oak woodland itself. Although wind direction influenced the numbers of moths that were captured in pheromone traps on woodland edges, with more moths captured in traps positioned on sheltered north‐facing edges, the differences in trap catches between north, south, east and west edges were not significant. The results from the present study indicate that a greater emphasis should be taken to deploy pheromone traps for oak processionary moth in the canopies of pedunculate oak trees with an open, sunnier disposition rather than within the interior of the forest or woodland, thereby maximizing their efficiency.